Investigation of gender-driven information processing strategies and the perceptions of pictorial warning labels. - Goh, Bee Poh. (2008)
The primary purpose of this research is to determine whether there is a significant relationship between gender-driven (left or right hemispheric dominant)information processing strategies and the perception of pictorial warning labels. Data were collected from a sample of 126 male and 178 female respondents,on a quota convenience basis, from a university campus. In general, it was found that right hemispheric dominants do indeed notice the iconic warning label more than their more logical left hemispheric counterparts. Furthermore, the research also demonstrated that right dominants are also more likely to comply with warning instructions in the case of the written version. This effect is also found to be much stronger for the iconic warning label.